Global perspectives, local impact: Chinese students’ role in global higher education - Li, Xuefan; Li, Tingsong; Li, Donghua; Zhou, Xiaoxu; Cheng, Yuxiang (Journal of International Students, 2026)
This study offers a comprehensive analysis of the multifaceted role of Chinese international students in the global higher education landscape from the unique perspective of policymakers. As the first comprehensive postpandemic qualitative study of its kind, it provides insights through interviews with policymakers and admission officers across 11 countries on four continents. Research reveals that while Chinese students are consistently perceived as significant contributors across economic, cultural, and academic domains, their integration is accompanied by inherent complexities and challenges. The findings highlight how countries are adapting their educational policies to navigate both the substantial impacts and the diverse difficulties faced by these students, underscoring the critical need for adaptive, inclusive, and responsive policies in the evolving post-pandemic era.